Almost contra-sgp-cleavability - A. Jallalh, Ghazeel (Libyan Journal of Science &Technology, 2024)
In this paper we introduce basic definitions and some properties, of special mapping called “almost contra sgp continuous” used to show the concept of cleavability over some special topological spaces as (sgp - , sgp- sgp - , weakly Hausdorff, Ultra Hausdroff, Ultra normal, sgp –normal, sgp- Ultra –connected ,hyper connected, sgp –compact–sgp- compact, sgp- Lindelöf, S-Lindelöf, S-closed) spaces.